2012
DOI: 10.1002/ijc.27837
|View full text |Cite
|
Sign up to set email alerts
|

Optical molecular imaging detects changes in extracellular pH with the development of head and neck cancer

Abstract: Non-invasive localized measurement of extracellular pH in cancer tissues can have a significant impact on the management of cancer. Despite its significance, there are limited approaches for rapid and non-invasive measurement of local pH in a clinical environment. In this study, we demonstrate the potential of noninvasive topical delivery of Alexa-647 labeled pHLIP (pH responsive peptide conjugated with Alexa Fluor® 647) to image changes in extracellular pH associated with head and neck squamous cell carcinoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 44 publications
1
31
0
Order By: Relevance
“…Given the close correspondence of the pH of the tumor microenvironment to pHLIPs’ pK ins , pHLIPs preferentially accumulate in tumors relative to healthy tissues, which generally exhibit local environments of pH 7.4. Fluorescently labeled pHLIPs have so far been shown in eleven published studies to accumulate in tumors with a high degree of contrast to healthy tissues (612, 1518). …”
Section: Biological Targeting Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Given the close correspondence of the pH of the tumor microenvironment to pHLIPs’ pK ins , pHLIPs preferentially accumulate in tumors relative to healthy tissues, which generally exhibit local environments of pH 7.4. Fluorescently labeled pHLIPs have so far been shown in eleven published studies to accumulate in tumors with a high degree of contrast to healthy tissues (612, 1518). …”
Section: Biological Targeting Activitymentioning
confidence: 99%
“…pH-Low Insertion Peptides (pHLIPs) are being developed for applications in several biomedical fields to exploit their specific biodistribution into tumors and other acidic tissue microenvironments, including drug delivery (15), in vivo imaging (617) and diagnostic histology (18), as well as in basic research (1924). pHLIP peptides target acidic tissues such as tumors due to a serendipitous biophysical coincidence.…”
Section: Introductionmentioning
confidence: 99%
“…We have introduced family of pHLIP ® peptides with pK of insertion varying from 4.5 to 6.5 [10]. The targeting of primary tumors by pHLIP ® peptides and delivery imaging and therapeutic agents has been demonstrated on more than 10 varieties of human and murine tumors [1517], including lymphoma [18], pancreatic [19], breast [2021] and prostate [22] transgenic mouse models and human head/neck biopsy samples [2324]. It was confirmed that tumor targeting by pHLIP ® peptides is indeed pH-dependent and could be modulated by bicarbonate and glucose, which affects tumor acidity [15, 2021, 2526].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical applications have focused on the topical application of pHLIP onto biopsies from human head and neck cancer patients, where pHLIP detected cancerous tissue within the samples (46,47).…”
mentioning
confidence: 99%